The Influence of Organizational Culture and Visionary Leadership on Instructor Innovation at the Vocational Training and Productivity Center in the Ministry of Manpower - Widodo, Gian Yekti; Notosudjono, Didik; Suhendra, Suhendra (Peneliti.net, 2023)
The purpose of this research is to find ways and strategies to enhance innovation for the achievement of organizational goals through the identification and strengthening of Organizational Culture and Visionary Leadership variables. This study employs a survey method with a quantitative approach, with a sample of 142 respondents. The data collection technique involves the use of a questionnaire. The data analysis steps in this research include: First, analyzing the correlation and linear regression aspects of each pair of variables and second, calculating the path coefficient using the product-moment correlation coefficient between each pair of research variables. The results indicate that (1) there is a direct positive influence between Organizational Culture (X1) and Innovation (Y); (2) there is a direct positive influence between Visionary Leadership (X2) and Innovation (Y). The conclusion of this research states that organizational culture and visionary leadership have a positive influence on innovation.